Experiences in implementing immunopsychiatry in real life - Janet L. Cunningham; Gunnel Nordmark; David Fällmar; Simon Cervenka; Maike Gallwitz; Roland Säll; Peter T. Schmidt; Johan Rönnelid; Barbro Persson; Andreas Kindmark; Joachim Burman (Journal of Affective Disorders Reports, 2023)
Immunological mechanisms, both alone and in combination, are associated with a broad range of psychiatric disorders encompassing autoimmune, autoinflammatory disorders but also genetic, metabolic, or other immunological disorders. Early treatment improves the outcome for autoimmune disorders, but early diagnosis is more difficult when isolated psychiatric symptoms are manifestations of autoimmunity. Treatment of these cases must encompass integrated models of disease, as both systemic autoimmunity and psychological processes influence mental health. Several challenges need to be overcome to efficiently merge psychiatric and somatic disease paradigms and medical care ranging from language and conceptual barriers to organizational barriers. Since 2015, the Immunopsychiatry team at Uppsala University has developed a collaborative multidisciplinary approach to improve and integrate care for patients with moderate to severe psychiatric disorders. Based on this experience, we have outlined the obstacles to be overcome in taking steps forward to achieve the long-term goal of understanding and early detection and identification of treatable immunological conditions within the psychiatric patient population; the described framework of evaluations and work-flow may serve as a model for other centers.